2014
DOI: 10.1158/1078-0432.ccr-13-1881
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Cediranib in Patients with Advanced Gastrointestinal Stromal Tumors or Soft-Tissue Sarcoma

Abstract: Purpose: Cediranib is a potent VEGF signaling inhibitor with activity against all three VEGF receptors and KIT. This phase II study evaluated the antitumor activity of cediranib in patients with metastatic gastrointestinal stromal tumor (GIST) resistant/intolerant to imatinib, or metastatic soft-tissue sarcomas (STS; ClinicalTrials.gov, NCT00385203).Experimental Design: Patients received cediranib 45 mg/day. Primary objective was to determine the antitumor activity of cediranib according to changes in 2[18F]fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…Their study showed 2 confirmed PR cases and 22 patients with SD. A phase II clinical trial was conducted to assess the activity of cediranib in patients with metastatic GIST or soft-tissue sarcoma who were resistant or intolerant to IM [89]. Changes in 2[18F]fluoro-2-deoxy-D-glucose positron emission tomography ( 18 FDG-PET) were used to determine the antitumor activity of cediranib using maximum standardized uptake values (SUV max ).…”
Section: Vascular Endothelial Growth Factor Inhibitorsmentioning
confidence: 99%
“…Their study showed 2 confirmed PR cases and 22 patients with SD. A phase II clinical trial was conducted to assess the activity of cediranib in patients with metastatic GIST or soft-tissue sarcoma who were resistant or intolerant to IM [89]. Changes in 2[18F]fluoro-2-deoxy-D-glucose positron emission tomography ( 18 FDG-PET) were used to determine the antitumor activity of cediranib using maximum standardized uptake values (SUV max ).…”
Section: Vascular Endothelial Growth Factor Inhibitorsmentioning
confidence: 99%
“…While most patients require surgery with an R0 resection for local control, the high rate of metastasis would indicate systemic therapy. However, it is thought that these tumors are chemoinsensitive, but early reports have demonstrated response to antiangiogenic therapies such as cediranib, bevacizumab, and sunitinib …”
Section: Introductionmentioning
confidence: 99%
“…Cediranib is a TKI with activity against VEGFR1–3 and KIT that has been investigated in GIST and STS and caused reduced FDG-PET activity in four out of six patients with ASPS but no overall reductions in SUVmax 96. A larger Phase II prospective trial found an ORR of 35% and a disease control rate of 84% at 24 weeks in patients with ASPS treated with single-agent cediranib 97.…”
Section: Tkismentioning
confidence: 99%